Excessive Bright Echoes Sign for Hypertrophic Pyloric Stenosis Suggest the Diagnosis: Gastric Pneumatosis and Portal Venous Gas in Infants Suggest HPS. (10th March 2017) - Cohen, Harris L.; Chism, P. Blake; Radtke, Ina
Abstract : We describe a new finding, the "excessive bright echoes" sign, for the diagnosis of hypertrophic pyloric stenosis (HPS). Portal venous gas and gastric wall pneumatosis were noted in 4 vomiting infants proven to have HPS. Portal venous gas can be concerning for ischemic bowel. Gastric wall pneumatosis can be seen in association with necrotizing enterocolitis and has been associated with increased gastric pressure from severe, usually proximal, bowel obstruction. Our HPS cases had prominent bright punctate echoes on sonography of the liver, portal vein lumen, and gastric wall. Knowledge of this excessive bright echoes sign suggests the need for sonography of the antropyloric area. One should consider HPS as a differential diagnostic possibility when the combination of bright echoes within the liver parenchyma, consistent with portal venous gas, and bright echoes in the gastric wall, consistent with gastric pneumatosis, are seen.